2010
DOI: 10.1193/1.3459153
|View full text |Cite
|
Sign up to set email alerts
|

Cracking an Open Safe: Uncertainty in HAZUS-Based Seismic Vulnerability Functions

Keith Porter

Abstract: The “cracking an open safe” methodology has been used to tabulate HAZUS-based seismic vulnerability as functions of structure-independent intensity, while avoiding iteration in the structural analysis. The vulnerability functions give mean damage factor (MDF, defined here as mean repair cost as a fraction of replacement cost) versus 5%-damped elastic spectral acceleration response at 0.3-second and 1.0-second periods, for every combination of occupancy type, model building type, design level, magnitude, distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…It is observed that COV tends to decrease with increase in MDR, a similar trend also observed elsewhere [55], and there is little dependence on the magnitude of earthquakes. On the other hand the standard deviation is found to behave differently where initially the standard deviation increases with increasing MDR, as observed elsewhere [55], up to certain level but then tends to saturate when the MDR gets very higher. The values of COV and standard deviation at a given MDR are different than the reported one [55].…”
Section: Uncertainties In Mdrsupporting
confidence: 86%
See 2 more Smart Citations
“…It is observed that COV tends to decrease with increase in MDR, a similar trend also observed elsewhere [55], and there is little dependence on the magnitude of earthquakes. On the other hand the standard deviation is found to behave differently where initially the standard deviation increases with increasing MDR, as observed elsewhere [55], up to certain level but then tends to saturate when the MDR gets very higher. The values of COV and standard deviation at a given MDR are different than the reported one [55].…”
Section: Uncertainties In Mdrsupporting
confidence: 86%
“…On the other hand the standard deviation is found to behave differently where initially the standard deviation increases with increasing MDR, as observed elsewhere [55], up to certain level but then tends to saturate when the MDR gets very higher. The values of COV and standard deviation at a given MDR are different than the reported one [55]. It is worth mentioning that other reported findings [55] are for different regions and structural systems which gives an indication that COV and standard deviation in loss estimation studies are structural and regional dependent.…”
Section: Uncertainties In Mdrsupporting
confidence: 72%
See 1 more Smart Citation
“…However, there is not any information in HAZUS related to a dispersion measure. Porter [2010] proposed a method for the determination of loss coefficient of variation (COV) using the expected value information provided by HAZUS. To determine the COV for the structure in consideration, engineers can obtain guidance from professional cost estimators .…”
Section: Loss Analysismentioning
confidence: 99%
“…Although initial studies on the generation of fragility curves for bridges in California were focused on empirical fragility curves (Shinozuka et al 2000), fragility curves have been generated using extensive numerical analyses over the last decades (Basöz and Mander 1999;Brandenberg et al 2011;Gardoni et al 2002;HAZUS-MH 2003;Huo and Zhang 2013;Mackie and Stojadinovic 2001;Mangalathu 2017;Mangalathu and Jeon 2018;Mangalathu et al 2018a;Ramanathan 2012;Zhong et al 2009). Although HAZUS is the only document, which suggests fragility relationships for all the bridge classes in California, the HAZUS methodology and fragility relationships are criticized by recent researches (Mangalathu et al 2017b;Porter 2010;Ramanathan 2012). The downside of the above cited studies is that the studies did not address the effect of near-fault (NF) and far-field (FF) ground motions separately.…”
Section: Introductionmentioning
confidence: 99%